Designing proteins with life sustaining activities 2 - Hecht, Michael (Henry Stewart Talks, 2017)
Novel designed proteins: mechanism of action, Function rescue experiments using novel proteins, Evolving novel proteins (generalists vs. specialists), Towards artificial proteomes capable of sustaining life